DIFFERENCES IN THE EFFECTIVENESS OF THE DIRECT DEMONSTRATION METHOD AND VIDEO SCREENING OF FIRST AID IN TRAFFIC ACCIDENTS ON THE INCREASE IN KNOWLEDGE OF SENIOR HIGH SCHOOL STUDENTS - Yustina Ni Putu Yusniawati; I Wayan Agus Maharyawan; Ahmad Robani (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2020)
Background: Traffic accidents are unpredictable collisions among vehicles that might lead to casualties. Injuries due to traffic accidents have killed at least 1.2 million lives per year. Fatalities are high as first aid is not properly administered, causing to higher mortality rate.Objectives: This research compared the effectiveness between the use of live demonstration and videos on high school students’ first aid knowledge.Methods: The research was conducted in the form of a comparative study with a cross sectional approach, for three months, starting from March to June 2019 in Senior High School 1 Rendang Karangasem Bali. The sample taken as many as 150 people as respondents who were divided into 2 groups, namely group 1 attended counseling which featured live demonstrations, while group 2 attended counseling where video was used as a medium. The instrument used was a questionnaire modified by researchers from Gorucu-Coskuner, H., Atik, E., & Taner, T. (2020) with 24 question items with yes and no answers. The validity test was carried out using the Pearson product-moment bivariate correlation technique where these results indicate that the value of